Glowing, glowing, gone? Monitoring long‐term trends in glow‐worm numbers in south‐east England. Issue 2 (4th March 2020) - Gardiner, Tim; Didham, Raphael K.
Abstract: The glow‐worm Lampyris noctiluca (Linnaeus, 1767) (Coleoptera: Lampyridae) is thought to be declining in the United Kingdom. Yet, much of the evidence for this is anecdotal, with a shortage of standardised long‐term data to investigate temporal changes in abundance. We present an 18‐year time series of standardised transect surveys for glowing adult females at 19 sites within south‐east England (Essex) from 2001 to 2018. We used generalised additive mixed models (GAMMs) to control for varying sampling effort, temporal autocorrelation, non‐stationarity of seasonal phenology and non‐linearity of temporal trajectories across sites. We found a significant long‐term reduction in counts of glowing female glow‐worms, after accounting for a significant shift in seasonal phenology across years, and a negative effect of warmer climatic conditions on glow‐worm abundance. Average glowing counts in south‐east England declined by ca. −3.5% per annum from 2001 to 2018, and this result held true even after a range of sensitivity tests to account for potential methodological artefacts in citizen science data collection. Temporal trajectories in abundance were strikingly out of phase across the 19 sites, suggesting that local‐scale factors in addition to climate are driving greater reduction in numbers at some sites than others. These standardised surveys present the first quantitative evidence that numbers of glow‐worms could well be declining in the United Kingdom. There is a clear signal of climate warming and drying effects on glow‐worm numbers, but a substantially greater proportion of variation in glowing female counts is explained by local‐scale site factors, such as unmanaged scrub encroachment. Conservation strategies that can mitigate local population losses could be an essential buffer against climate‐driven declines in south‐east England. Abstract : The glow‐worm Lampyris noctiluca is thought to be declining. We present standardised transect surveys for glowing adult females at 19 sites within south‐east England (Essex) from 2001 to 2018. We found a significant long‐term reduction in counts of glowing females, after accounting for a significant shift in seasonal phenology, and negative effect of warmer climatic conditions on abundance. These surveys present the first quantitative evidence that glow‐worms may be declining in England. Climate warming and local‐scale site factors, such as unmanaged scrub encroachment, could reduce glow‐worm numbers.